User evaluation of a novel eye-based control modality for robot-assisted object retrieval. (3rd April 2017) - Li, S.; Webb, J.; Zhang, X.; Nelson, C. A.
Graphical Abstract: Abstract: In recent years, great efforts have been put into the investigation of assistive robotics. However, rapid growth in robot functionality has caused control of these robots to become more complex. Natural interaction interfaces between the user and robot systems are highly desired to promote the usability of these robots in practical applications. This paper presents a novel intuitive gaze-based system, which enables a user to effectively command an assistive robot with his/her gaze. This system has the potential to help those, who have limited mobility and/or are confined in bed, with their daily living. Using this system, the object that needs to be manipulated can be directly identified and localized by simply looking at it by the user. Then the assistive robot is activated to perform appropriate manipulation of the object. In the experiments, participants were able to successfully accomplish the object retrieval tasks using the presented system. Moreover, results from subjective evaluation showed high usability of the presented system.